The influence of board and firm characteristics on the implementation of integrated reporting in financial services companies registered in BEI - Dewa Ayu Intan Maheswari; Sufiyati Sufiyati (Institute of Computer Science (IOCS), 2023)
The integrated reporting framework is a framework that is used in the implementation of an integrated reporting. This framework consists of a number of financial reports, management records, corporate governance and remuneration, as well as a sustainability report. This conceptual framework is able to explain how companies create value for themselves. This study aims to analyze the factors that influence the implementation of integrated reporting of a company. Through non-probability sampling technique with purposive sampling method, 21 companies were obtained as samples and 42 data were used for observation. Then, the data was processed using SPSS 25 version for panel data regression analysis. The results of the study indicated that the projected board size, as measured by the total number of directors, and the projected board meetings, as measured by the number of combined board members' meetings in one year, have a positive and significant influence on the implementation of integrated reporting. Board independence and leverage have a positive and insignificant influence on the implementation of integrated reporting. Meanwhile, firm size has a negative and insignificant influence on the implementation of integrated reporting. Further research is expected to add other variables to improve previous studies